The role of the labor inspectorate in the prevention of psychological and social risks - Maakouf, Mouna (Journal of Human Sciences, 2022)
The labor inspectorate is specialized in monitoring compliance with the implementation of legislative and regulatory provisions, especially those related to health and security within the enterprise. It also has an important role in preventing occupational hazards that may afflict workers in workplaces, where labor inspectors have the right to visit and enter workplaces at any hour of the night or Al-Nahar in order to monitor the application of the provisions related to occupational health and safety, and they can also carry out examination and investigation by looking at records, including in the field of health prevention, security, work medicine, and the record of work accidents, and in the event that the labor inspector notices a default or violation of the law, he sends an excuse to the user or edits Violation record.